Small To Medium Enterpirses In The Digital Era On Line Shop Professional Community (Kaji) In East Java - Idham, Idham; Made, Henni; Dewi Fitrianingsih, Sri; Bin Mukhtar, Dzulkifli (Publisher Cv. Inara, 2024)
Small To Medium Enterpirses In The Digital Era On Line Shop Professional Community (Kaji) In East Java. The contribution of SMEs has had an impact on the regional and national economy (Bunga, 2022), the growth and development of SMEs in Indonesia cannot be separated from the various challenges faced, the economic crisis that occurred at the end of 1997 brought multi-economic impacts, including SMEs (Tejasari, 2008), the impact of Covid 19 which occurred in early 2020, the impact of the global economy occurred as a whole. SMEs also felt the same impact with the independence that SMEs have, being able to overcome global economic challenges (Aksan, 2022), entering the digital era. East Java UKM (KAJI) is faced with online shop UKM must be able to take a role and control the market so that the existence of SMEs is not eroded by digitalization, especially online shops. Legitimacy theory focuses on interactions between companies and society based on legitimacy theory, namely that a